Relationship of dose to vascular target volumes and local failure in pancreatic cancer patients undergoing neoadjuvant chemoradiation - Nelson, Bailey; Barrord, Michelle; Wang, Kyle; Wages, Nolan A.; Sudhoff, Mickaela; Kharofa, Jordan (Frontiers in Oncology, 2022)
Objective The objectives of this study were to evaluate whether dose to the vasculature is associated with local control after surgery in patients with borderline resectable (BLR) and resectable pancreatic cancer (PCA) receiving neoadjuvant radiation therapy (RT) and to identify a dose threshold for clinical use. Methods Patients with BLR and resectable PCA treated with neoadjuvant RT were retrospectively reviewed. During this period, the institutional paradigm shifted from standard fractionation to hypofractionation/stereotactic body radiation therapy (SBRT). A vasculature clinical target volume (Vasc CTV) was contoured for each patient and defined as a 5-mm margin around the superior mesenteric artery (SMA) from its origin to the pancreatic head, the celiac artery from its origin to the level of the trifurcation and any involved vein. The Vasc CTV D95 was normalized to a 2-Gy equivalent dose to determine the optimal dose associated with optimal local failure-free survival (LFFS). Results Forty-seven patients were included in the analysis. A Vasc CTV D95 of 32.7 Gy was the optimal cutoff for LFFS. Patients with Vasc CTV D95 Equivalent dose in 2 Gy per fraction (EQD2) >32.7 Gy had significantly longer LFFS compared to patients with Vasc CTV D95 EQD2 ≤32.7 Gy at 12 months (91% vs. 51%, respectively) and 24 months (86% vs. 12%, respectively). The median disease-free survival (DFS) for patients with EQD2 >32.7 Gy was 30.4 months compared to 14.0 months in patients with EQD2 ≤32.7 Gy (p = 0.01). There was no significant difference in overall survival (OS) between the two groups. Conclusions During neoadjuvant treatment, dose to the Vasc CTV is associated with durability of local control (LC) after resection and should be intentionally included in the treatment volume with an EQD2 goal of 31–33 Gy.